Deterministic Assembly of Flexible Si/Ge Nanoribbons via Edge‐Cutting Transfer and Printing for van der Waals Heterojunctions. Issue 33 (12th May 2015) - Guo, Qinglei; Zhang, Miao; Xue, Zhongying; Wang, Gang; Chen, Da; Cao, Ronggen; Huang, Gaoshan; Mei, Yongfeng; Di, Zengfeng; Wang, Xi
<x xml:space="preserve">Abstract</x> As the promising building blocks for flexible electronics and photonics, inorganic semiconductor nanomembranes have attracted considerable attention owing to their excellent mechanical flexibility and electrical/optical properties. To functionalize these building blocks with complex components, transfer and printing methods in a convenient and precise way are urgently demanded. A combined and controllable approach called edge‐cutting transfer method to assemble semiconductor nanoribbons with defined width (down to submicrometer) and length (up to millimeter) is proposed. The transfer efficiency can be comprehended by a classical cantilever model, in which the difference of stress distributions between forth and back edges is investigated using finite element method. In addition, the vertical van der Waals PN (p‐Si/n‐Ge) junction constructed by a two‐round process presents a typical rectifying behavior. The proposed technology may provide a practical, reliable, and cost‐efficient strategy for transfer and printing routines, and thus expediting its potential applications for roll‐to‐roll productions for flexible devices.